2016
DOI: 10.1104/pp.15.01232
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Starch Synthase IIIa and IVb Alters Starch Granule Morphology from Polyhedral to Spherical in Rice Endosperm

Abstract: Starch granule morphology differs markedly among plant species. However, the mechanisms controlling starch granule morphology have not been elucidated. Rice (Oryza sativa) endosperm produces characteristic compound-type granules containing dozens of polyhedral starch granules within an amyloplast. Some other cereal species produce simple-type granules, in which only one starch granule is present per amyloplast. A double mutant rice deficient in the starch synthase (SS) genes SSIIIa and SSIVb (ss3a ss4b) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
110
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 57 publications
1
110
0
Order By: Relevance
“…The mechanism of starch granule initiation in developing rice grains may differ in some ways from that in Arabidopsis leaves. In amyloplasts of rice endosperm, granules form from multiple initiation centers that are held together into larger structures, so-called compound granules (Matsushima et al, 2013;Toyosawa et al, 2016). Rice flo6 mutants have reduced starch content in the grain, altered physicochemical properties of starch, and minor changes in the chain length distribution of amylopectin.…”
Section: Ptst2/flo6 Is a Potential Target For The Biotechnological Momentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of starch granule initiation in developing rice grains may differ in some ways from that in Arabidopsis leaves. In amyloplasts of rice endosperm, granules form from multiple initiation centers that are held together into larger structures, so-called compound granules (Matsushima et al, 2013;Toyosawa et al, 2016). Rice flo6 mutants have reduced starch content in the grain, altered physicochemical properties of starch, and minor changes in the chain length distribution of amylopectin.…”
Section: Ptst2/flo6 Is a Potential Target For The Biotechnological Momentioning
confidence: 99%
“…It is also important to note that a rice mutant deficient in the major isoform of SS4 in the endosperm (SS4b) has relatively minor alterations in starch content and granule morphology (Toyosawa et al, 2016). Therefore, it would not be easy to explain how altered SS4 activity would cause the flo6 phenotype.…”
Section: Ptst2/flo6 Is a Potential Target For The Biotechnological Momentioning
confidence: 99%
“…However, studies with ssIV mutants in the endosperm of japonica rice show very different effects on storage starch synthesis. An ssIV mutant lacking SSIVb showed no noticeable effect on endosperm starch content or structure, although a ssIII/ssIV double mutant, though being able to produce starch, formed single, loose spherical granules, as opposed to compact, compound granules that are characteristic of many members of the Ehrhartoideae (e.g., Oryza and Microlaena (=Ehrharta) species, see Figure 1) [255]. The function of SSIV may require an unusual sub-plastidial environment, as localization studies in Arabidopsis chloroplasts showed SSIV interacts with fibrillins that are hydrophobic proteins localized to plastidial lipid bodies, termed plastoglobules [256].…”
Section: Soluble Starch Synthasesmentioning
confidence: 99%
“…The localization of SSIV in lipid/membrane structures may also provide a clue as to its function in storage starch biosynthesis. It was hypothesized by Toyosawa et al [255] that SSIV may localize to the membrane-like environment of cross walls (septa) dividing compound starch granules in the Ehrhartoideae. The septa of compound granules contain plastid division proteins such as FtsZ, Min, and PDV2 [258], and the loss of SSIV in the rice mutant (above) may disrupt normal compound granule formation, as observed in the ssIV mutant [255].…”
Section: Soluble Starch Synthasesmentioning
confidence: 99%
“…Zhou et al also examined the RS content of two japonica loss-of-function (ssIIIa) mutants, one of which was previously reported as flo5-1 (7). Zhou et al (6) find that b10 had altered starch granule structure, namely, the transition from normally polyhedral starch granules in wild-type to rounded, variably sized, and irregularly surfaced ones like those in earlier ssIIIa mutants (8). This internal structure apparently influences the overall appearance of the mutant grains, which exhibit white cores (7,8).…”
mentioning
confidence: 99%